Pathogenic variants damage cell composition and single-cell transcription in cardiomyopathies - Reichart,D; Lindberg,EL; Maatz,H; Miranda,AMA; Viveiros,A; Shvetsov,N; Gaertner,A; Nadelmann,ER; Lee,M; Kanemaru,K; Ruiz-Orera,J; Strohmenger,V; et al. (Science, 2022)
INTRODUCTIONHuman heart failure is a highly morbid condition that affects 23 million individuals worldwide. It emerges in the setting of an array of different cardiovascular disorders, which has propelled the notion that diverse stimuli converge on a common final pathway. Consistent with this, initiating etiologies do not direct heart failure treatments, which are often inadequate and necessitate mechanical interventions and cardiac transplantation.The recent application of single-nucleus RNA sequencing (snRNAseq) transcriptional analyses to characterize the cellular composition and molecular states in the healthy adult human heart provides an emerging benchmark by which disease-related changes can be assessed. Moreover, the discovery of human pathogenic variants that cause dilated cardiomyopathy (DCM) and arrhythmogenic cardiomyopathy (ACM), disorders associated with high rates of heart failure, provides direct opportunities to evaluate whether genotype influences heart failure pathways.RATIONALEA systematic identification of shared and distinct molecules and pathways involved in heart failure is lacking, and knowledge of these fundamental data could propel the development of more effective treatments. To enable these discoveries, we performed snRNAseq of explanted ventricular tissues from 18 healthy donors and 61 heart failure patients. By focusing analyses on multiple samples with pathogenic variants in DCM genes (LMNA, RBM20, and TTN), ACM genes (PKP2), or pathogenic variant–negative (PV negative) samples, we characterized genotype-stratified and common heart failure responses.RESULTSFrom 881,081 nuclei isolated from left and right diseased and healthy ventricles, we identified 10 major cell types and 71 distinct transcriptional states. DCM and ACM tissues showed significant depletion of cardiomyocytes and increased endothelial and immune cells. Fibrosis was expanded in disease hearts, but, unexpectedly, fibroblasts were not increased, and instead showed a